Knowledge and attitudes to prevent teenage pregnancy in a school in Loja, Ecuador - Godoy Ramón, Jhegner David; Zaquinaula Jirón, Iván Enrique; Tamayo Cumbicus, Jenny Elizabeth; Gómez Salgado, Diana Margarita; Ortiz Yunga, Jilmar Fabricio; Zula Riofrio, Paúl David (Enfermería Cuidándote, 2026)
Introduction: Adolescence is crucial for human development, but teenage pregnancy affects health, society and economy, especially in young people with little education and resources.General objective: To determine the level of knowledge and attitudes towards the prevention of adolescent pregnancy among students of the Pedro Vicente Maldonado Educational Unit.Method: The research had a quantitative approach, descriptive scope and cross-sectional design. The population consisted of 167 students, and the sample consisted of 117, selected by stratified probability sampling. The survey was used as a data collection technique, and a validated and reliable questionnaire was used to evaluate knowledge and attitudes.Results: The predominant sex was female, representing 60.7% of the participants, and the most common age group was middle adolescence, with 59.8%. Most of the students came from nuclear households (76.9 %), and the most practiced religion was Catholic (96.6 %). Regarding the level of knowledge about the prevention of adolescent pregnancy, 54.7% of the participants showed medium knowledge, while 30.8% showed a high level and 14.5% showed low knowledge. Regarding attitudes, no significant difference was observed, since 53.8 % adopted unfavorable attitudes, while 46.2 % manifested favorable attitudes on the subject.Conclusions: It is concluded that the lack of knowledge about adolescent pregnancy can lead students to adopt unfavorable attitudes towards this problem.
Keywords: Adolescence; Pregnancy in Adolescence; Reproductive Health; Reproductive Rights; Responsibility; Sexuality